Study Motility of Ongole Crossbred Semen with Soybean-Based Diluents Stored at Ambient Temperature (24-27 0C) - Dian Ratnawati; Gatot Ciptadi; sri rahayu; trinil susilawati (Jurnal Ilmu-Ilmu Peternakan, 2023)
Artificial insemination with fresh semen is an alternative that can be done if there is a limitation of liquid nitrogen, bull, and facilities for processing liquid and frozen semen (costly). This study aimed to determine the optimal diluent formula based on CEP-3 (modified/m) and aqueous soybean extract (ASE) to support spermatozoa motility at ambient temperature storage. The research design was completely randomized, with eight treatments and six replications. The diluent formula treatments were as follows: T1 (CEP-3(m)), T2 (CEP-3(m)+10% Egg Yolk/EY), T3 (CEP-3(m)+ASE 1%), T4 (CEP-3 (m)+ASE 2%), T5 (CEP-3(m)+ASE 3%), T6 (CEP-3(m)+ASE 4%), T7 (CEP-3(m)+ASE 5%), and T8 (CEP-3(m)+ASE 6%). The parameters were measured, i.e., the motility of spermatozoa and its kinetic parameters. Data were analyzed using ANOVA with SPSS 16 program. The result showed that the progressive motility of spermatozoa at day one was more than 50% in diluents CEP-3(m)+ASE 1-2%. Diluent CEP-3(m) and aqueous soybean extract 1-2% can support spermatozoa's motility and kinetic parameters during storage at ambient temperature, including progressive motility, motility, motility, velocity, and BCF.